Mechanism of the Intracellular Killing and Modulation of Antibiotic Susceptibility of Listeria monocytogenes in THP-1 Macrophages Activated by Gamma Interferon - Ouadrhiri, Youssef (American Society for Microbiology, 1999)
Listeria monocytogenes, a facultative intracellular pathogen, readily enters cells and multiplies in the cytosol after escaping from phagosomal vacuoles. Macrophages exposed to gamma interferon, one of the main cellular host defenses against Listeria, become nonpermissive for bacterial growth while containing Listeria in the phagosomes. Using the human myelomonocytic cell line THP-1, we show that the combination of l-monomethyl arginine and catalase restores bacterial growth without affecting the phagosomal containment of Listeria. A previous report (B. Scorneaux, Y. Ouadrhiri, G. Anzalone, and P. M. Tulkens, Antimicrob. Agents Chemother. 40:1225–1230, 1996) showed that intracellular Listeria was almost equally sensitive to ampicillin, azithromycin, and sparfloxacin in control cells but became insensitive to ampicillin and more sensitive to azithromycin and sparfloxacin in gamma interferon-treated cells. We show here that these modulations of antibiotic activity are largely counteracted by l-monomethyl arginine and catalase. In parallel, we show that gamma interferon enhances the cellular accumulation of azithromycin and sparfloxacin, an effect which is not reversed by addition of l-monomethyl arginine and catalase and which therefore cannot account for the increased activity of these antibiotics in gamma interferon-treated cells. We conclude that (i) the control exerted by gamma interferon on intracellular multiplication of Listeria in THP-1 macrophages is dependent on the production of nitric oxide and hydrogen peroxide; (ii) intracellular Listeria may become insensitive to ampicillin in macrophages exposed to gamma interferon because the increase in reactive oxygen and nitrogen intermediates already controls bacterial growth; and (iii) azithromycin and still more sparfloxacin cooperate efficiently with gamma interferon, one of the main cellular host defenses in Listeria infection.